Topology : - McCarty, George (McGraw-Hill, 1967)
Topology, sometimes described as "rubber-sheet geometry," is crucial to modern mathematics and to many other disciplines — from quantum mechanics to sociology. This stimulating introduction to the field will give the student a familiarity with elementary point set topology, including an easy acquaintance with the line and the plane, knowledge often useful in graduate mathematics programs.